Occurrence rate of equatorial Spread F and GPS ROTI in the ionospheric anomaly region over Vietnam - Pham Thi Thu, Hong; Christine Amory, Mazaudier; Le Huy, Minh; Susumu, Saito; Nguyen Thanh, Dung; Luong Thi, Ngoc; Luu Viet, Hung; Nguyen Chien, Thang; Nguyen Ha, Thanh; Michi, Nishioka; et al. (Vietnam Journal of Earth Sciences, 2024)
This paper presents the first observations of the occurrence rates of Spread F and GPS total electron content (TEC) index (ROTI) over Vietnam at the equatorial trough and the northern tropical crest of ionization anomaly in the Asian sector. The data have been examined for the monthly and nighttime variations in the occurrence of these two data at Bac Lieu (9.28°N, 105.73°E, dip: 1.73°N) and Phu Thuy (21.03°N, 105.95°E, dip: 14.49°N) during 2023. For Bac Lieu, the monthly variation in the occurrence of the range Spread F (RSF) has the maxima in the February, May, and September months, while the mixed Spread-F (MSF) and ROTI occurrences exhibit a semiannual asymmetry with peaks in March/April and October. For the nighttime variation, occurrence peaks at 1915-1930 LT for RSF, at about 1945-2100 LT for MSF, and between 2030-2330 LT for ROTI. Regarding the frequency Spread F (FSF) occurrence, the maximum values in the monthly variation are in April, and the nighttime variation peaks at about 2115-2315 LT. For Phu Thuy, the monthly variation of RSF, MSF, and ROTI occurrences also exhibit a semiannual asymmetry with peaks in March/April and October. These peak magnitudes are largest for ROTI, moderate for MSF, and smallest for RSF. The nighttime variation of RSF, MSF, and ROTI occurrence peaks show intense season changes from winter to autumn at pre-midnight, spring at post-midnight, and summer at post-midnight. The FSF occurrences are more significant in summer than in other seasons, mainly after midnight. The time order appearance of the Spread F types at Bac Lieu and Phu Thuy is first of RSF, then MSF, and finally FSF. This could reflect that the formation mechanisms of Spread F types are different and require further research. Our observations also showed that the post-midnight occurrence of Spread F is much larger than ROTI at Bac Lieu and Phu Thuy. The monthly variations in occurrence rates of Spread F and ROTI at Bac Lieu and Phu Thuy are similar, but these occurrence rates at Bac Lieu are usually larger than at Phu Thuy.